2013
DOI: 10.1007/s00418-013-1085-x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of somatic electromechanical force by outer hair cells may be influenced by prestin–CASK interaction at the basal junction with the Deiter’s cell

Abstract: The motor protein, prestin, situated in the basolateral plasma membrane of cochlear outer hair cells (OHCs), underlies the generation of somatic, voltage-driven mechanical force, the basis for the exquisite sensitivity, frequency selectivity and dynamic range of mammalian hearing. The molecular and structural basis of the ontogenetic development of this electromechanical force has remained elusive. The present study demonstrates that this force is significantly reduced when the immature subcellular distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Expression levels and voltage‐dependent characteristics of prestin can be assessed by electrophysiological recordings of charge movement or—equivalently—nonlinear capacitance (NLC), both resulting from prestin's voltage sensor . Since NLC amplitude and voltage dependence systematically change with postnatal development , NLC can also be used as a measure of OHC functional maturation . Normally, prestin expression reaches a mature level around p15 .…”
Section: Methodsmentioning
confidence: 99%
“…Expression levels and voltage‐dependent characteristics of prestin can be assessed by electrophysiological recordings of charge movement or—equivalently—nonlinear capacitance (NLC), both resulting from prestin's voltage sensor . Since NLC amplitude and voltage dependence systematically change with postnatal development , NLC can also be used as a measure of OHC functional maturation . Normally, prestin expression reaches a mature level around p15 .…”
Section: Methodsmentioning
confidence: 99%
“…In response to a change in its transmembrane potential (Brownell et al ., ; Ashmore, ; Dallos & Evans, ) the OHC produces electromechanical force (Frank et al ., ) to amplify the vibration response of the cochlea. The molecular basis of this electromechanical transducer is the motor protein prestin (Zheng et al ., ), located in the OHC basolateral plasma membrane (Kalinec et al ., ; Huang & Santos‐Sacchi, ; Cimerman et al ., ). Prestin is essential for cochlear amplification and, therefore, normal hearing (Liberman et al ., ; Dallos, ).…”
Section: Introductionmentioning
confidence: 97%
“…Yamashita and colleagues also reported that proteins in the OHC’s LM, including prestin, are virtually immobile ( Yamashita et al, 2015 ), suggesting that the prestin-embedded LM forms a distinct domain, separate from apical and basal membrane compartments. This unique arrangement of membrane domains appears to be functionally important, as hypothyroid animals, where prestin expression is observed along the entire basolateral membrane, have impaired hearing and reduced electromechanical force generation ( Cimerman et al, 2013 ). In this regard, prestin is the key intrinsic factor that separates motile OHCs from non-motile inner hair cells (IHC), which only have two (apical and basolateral) membrane compartments.…”
Section: Introductionmentioning
confidence: 99%